Under the color of law [large type] : a Kevin Kearney novel - McGarrity, Michael (Beeler Large Print, 2003)
Before police chief Kevin Kerney can discover who murdered a U.S. ambassador's estranged wife, the FBI takes over the investigation and the case is neatly solved, but Kerney is convinced that he is in the midst of an intelligence cover-up.